Reducing Sexual Harassment and Gender Discrimination: Recommendations for the Mexico City Police Department - Zeddies, Amber Elizabeth; Wincek, Zachary Joseph; Wang, Hsiu-Ching; Styles, Julia Larscheid; Schmitt, William James; Do, My Linh (My University, 2005)
To reduce sexual and gender discrimination, the Mexico City Policy Department could strengthen existing enforcement mechanisms, establish a legitimate external oversight body and encourage creation of female support networks, this report suggests.
For PA 860: Public Affairs Workshop, International Issues